Sugar flux and signaling in plant-microbe interactions - Bezrutczyk, Margaret; Yang, Jungil; Eom, Joon-Seob; Prior, Matthew; Sosso, Davide; Hartwig, Thomas; Szurek, Boris; Oliva, Ricardo; Vera Cruz, Casiana; White, Frank F.; Yang, Bing; Frommer, Wolf B. (Wiley, 2018)
Plant breeders have developed crop plants that are resistant to pests, but the continual evolution of pathogens creates the need to iteratively develop new control strategies. Molecular tools have allowed us to gain deep insights into disease responses, allowing for more efficient, rational engineering of crops that are more robust or resistant to a greater number of pathogen variants. Here we describe the roles of SWEET and STP transporters, membrane proteins that mediate transport of sugars across the plasma membrane. We discuss how these transporters may enhance or restrict disease through controlling the level of nutrients provided to pathogens and whether the transporters play a role in sugar signaling for disease resistance. This review indicates open questions that require further research and proposes the use of genome editing technologies for engineering disease resistance.